IMPROVING READING-ALOUD ABILITY WITH A CONSTRUCTIVISM APPROACH FOR GRADE 2 ELEMENTARY STUDENTS - Muhardila Fauziah; Yeni Sulaeman; Yuhardina Fauziah; Yeni Maizora (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper discusses the improvement of the reading-aloud ability of grade 2 elementary school students through a constructivism approach. The research uses the classroom action method, which begins with the pre-cycle stages, cycle 1 and cycle 2 where each stage includes planning, implementation, observation, and reflection. After carrying out the research procedures and collecting data, the results indicate that the reading-aloud ability of grade 2 students using the constructivism approach provided a significant increase in grade 2 elementary school students’ reading-aloud ability. The assessment indicators of reading-aloud ability were pronunciation, intonation, fluency, and students' courage, which describes an improvement in the students' reading-aloud ability test. The average pre-cycle score of students' reading-aloud ability was 67.85 increased to 73.53 in cycle 1. Subsequently, the average score increased to 80.23 in cycle 2. Based on the research results above, the researcher concludes that students' reading-aloud ability could be improved by using a constructivism approach for grade 2 elementary school students.